(untitled) (International Congress on Economics, Management and Business Studies, 2026)
Agriculture constitutes one of the most crucial sectors of the economy of the Republic of Uzbekistan, playing a central role in ensuring national food security, generating employment, and supporting rural livelihoods. Over the past decade, the agricultural sector has undergone substantial transformations as a result of comprehensive economic reforms, institutional restructuring, and increasing integration into global markets. These changes have been accompanied by a gradual shift from state-controlled production systems toward market-oriented mechanisms, diversification of crops, and the development of value-added agricultural chains.